Posterior single implants immediately loaded using one abutment at one time and temporary abutment in the posterior mandible without bone augmentation: a report on six-month outcomes data obtained from a prospective randomized controlled split-mouth clini - Marković, Jovana; Todorović, Ana; Ilić, Branislav; Marković, Aleksa; Živanović, Tanja; Veljković, Kristina; Milinković, Iva (Vojnosanitetski pregled, 2024)
Background/Aim. Given that frequent manipulation of the abutment during immediate loading can have a negative impact on the surrounding peri-implant hard and soft tissues, the concept “one abutment at one time” (OAO) has been introduced and documented in daily clinical practice. The aim of the study was to evaluate changes in peri-implant bone levels, clinical and radiographic parameters, and patient perspectives during the six-month follow-up period. Methods. The study was designed as a randomized controlled clinical trial. Patients with bilaterally healed sites in the posterior mandible received implants with a diameter of no less than 3.5 mm and a length of at least 8 mm. Based on randomization, patients were divided into a test group and a control group. Patients who were in the test group received implants that were immediately loaded with definitive abutments. In contrast, patients in the control group received implants where healing abutments were placed, followed by temporary abutments. Implants were immediately loaded with provisional restorations within the first seven days. They were delivered over the test group’s definitive abutment and the control group’s temporary abutment. Probing depth, bleeding on probing, clinical attachment level, plaque index, and keratinized tissue width were measured. Patient-Reported Outcome Measures and the Oral Health Impact Profile – 19 (OHIP-19) questionnaires were noted. Results. Out of 24 included patients, 22 completed the six-month follow-up. Peri-implant bone loss between study groups was comparable (mesial: t = -0.798, df = 21, p = 0.434; distal: t = 1.688, df = 21, p = 0.106), without statistical inter-group significance. OHIP-19 total scores significantly decreased after three months and remained similar six months after the implant placement in both groups without statistically relevant clinical inter-group changes. Conclusion. The OAO approach and provisional abutments showed comparable effectiveness regarding the immediate loading of posterior single implants.